Structural insight into the CUB2 domain’s role in enteropeptidase-mediated trypsinogen activation - Qiuyue Song; Lisi Peng; Xiaoli Yang; Jiaheng Xu; Deyu Zhang; Xiaorong Tian; Shiyu Li; Yang Zhang; Baoan Ji; Zhendong Jin; Zhanyu Ding; Zhaoshen Li; et al. (Proceedings of the National Academy of Sciences, 2026)
Elucidating the structure and function of enteropeptidase (EP) is essential for advancing our understanding of its biological significance, particularly in regulating trypsinogen activation. Using cryo-EM and enzymatic activity, we uncovered the significance of the CUB2 domain in mediating the cleavage of macromolecular substrates. We identified crucial binding loops and key residues for EP’s proteolytic function. The mutation E574A enhanced the proteolytic activity of EP, whereas the mutation N619A diminished its cleavage efficiency, highlighting the importance of surface-charged interactions in modulating EP’s activity. A proteolytic cycle was proposed to deepen our understanding of the trypsinogen activation by EP. This work offers valuable insights into the molecular mechanisms underlying EP’s interaction with its substrate, and opens up avenues for therapeutically modulating EP-mediated proteolysis.